FRI0410 TgfΒ promotes fibrosis by myst1-dependent epigenetic regulation of autophagy. (12th June 2018) - Zehender, A.; Lin, N.-Y.; Stefanica, A.; Chen, C.-W.; Soare, A.; Wohlfahrt, T.; Rauber, S.; Bergmann, C.; Ramming, A.; Distler, O.; Distler, J.
Abstract : Background: Autophagy is catabolic process allowing cells to degrade unnecessary or dysfunctional cellular organelles. Aberrant activation of autophagy has been also implicated into the pathogenesis of fibrotic diseases. Several stimuli present in fibrosis such as pro-fibrotic cytokines are known to activate autophagy. Objectives: The objective of this work is characterise the regulation of autophagy by TGFβ and analyse whether targeting of autophagy in fibroblasts may prevent their aberrant activation in fibrotic diseases. Methods: To selectively disable autophagy in fibroblasts we generate Atg7 fl/fl x Col1a2;Cre ER mice. The role of the autophagy was investigated in the model of bleomycin- and TβRIact-induced dermal and pulmonary fibrosis. Overexpression of Myst1 was achieved by adenovirus encoding for Myst1 . Collagen release and protein expression were measure by Western blot. Target genes were analysed by RT-PCR. Co-immunoprecipitation and reporter assay were performed to study physical and functional interactions between MYST1 and SMAD3. To monitor the autophagic flux in vitro and in vivo we generate an adenovirus encoding for tandem fluorescent-tagged LC3 (mRFP-EGFP-LC3), defined as reliable autophagy maker. Results: We provide evidence that transforming growth factor-β (TGFβ) activates autophagy by an epigenetic mechanism to amplify its profibrotic effects. TGFβ induces autophagy in fibrotic diseases by SMAD3-dependent downregulation of the H4K16-histoneacetlytransferase MYST1, which controls the expression of core components of the autophagy machinery such as ATG7 and BECLIN1. Activation of autophagy in fibroblasts promotes collagen release and is both, sufficient and required, to induce tissue fibrosis. Forced expression of MYST1 abrogates the stimulatory effects of TGFβ on autophagy and re-establishes the epigenetic control of autophagy in fibrotic conditions. Interference with the aberrant activation of autophagy inhibits TGFβ-induced fibroblast activation and ameliorates experimental dermal and pulmonary fibrosis. These findings link uncontrolled TGFβ signalling to aberrant autophagy and altered epigenetics in fibrotic diseases and may open new avenues for therapeutic intervention in fibrotic diseases. Conclusions: We demonstrate that the epigenetic control of autophagy is disturbed by a TGFβ-dependent downregulation of MYST1. The increased activation of autophagy induces fibroblast-to-myofibroblast transition and promotes fibrotic tissue remodelling. Re-expression of MYST1 prevents aberrant autophagy, limits the profibrotic effects of TGFβ and ameliorates experimental fibrosis. Restoration of the epigenetic control of autophagy might thus be a novel approach to ameliorate fibrotic tissue remodelling. Disclosure of Interest: A. Zehender: None declared, N.-Y. Lin: None declared, A. Stefanica: None declared, C.-W. Chen: None declared, A. Soare: None declared, T. Wohlfahrt: None declared, S. Rauber: None declared, C. Bergmann: None declared, A. Ramming: None declared, O. Distler Grant/research support from: Actelion, Pfizer, Ergonex, BMS, Sanofi-Aventis, United BioSource Corporation, Roche/Genentech, Medac, Biovitrium, Boehringer Ingelheim, Novartis, 4D Science, Active Biotech, Bayer, Sinoxa, Serodapharm, EpiPharm, GSK, Pharmacyclics and Biogen, Consultant for: Actelion, Pfizer, Ergonex, BMS, Sanofi-Aventis, United BioSource Corporation, Roche/Genentech, Medac, Biovitrium, Boehringer Ingelheim, Novartis, 4D Science, Active Biotech, Bayer, Sinoxa, Serodapharm, EpiPharm, GSK, Pharmacyclics and Biogen, J. Distler Shareholder of: 4D Science, Grant/research support from: Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis, UCB, Consultant for: Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Ga-lapagos, GSK, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi and UCB